Analysis of the VLE data in "Measurement and correlations of density, viscosity, and vapour-liquid equilibrium for fluoro alcohols". (April 2017) - Wisniak, Jaime; Ortega, Juan; Fernández, Luis
Highlights: A critical analysis on the published data in JCT 102 (2016) 155–163, is carried out. Different consistency tests are applied to the data used in this work for their thermodynamic evaluation. It concludes by questioning the quality of the published data. Abstract: The vapour-liquid equilibrium results reported by Zhang et al. [1] for the binary systems {methanol (1) + 2, 2, 3, 3, 4, 4, 5, 5-octafluoro-1-pentanol (2)} and {2, 2, 3, 3-tetrafluoro-1-propanol (1) + 2, 2, 3, 3, 4, 4, 5, 5-octafluoro-1-pentanol (2)} have been analysed using the data evaluation methodology published recently [2] and found to be unreliable.